Health Behavior of Essential Hypertension Patients in Public Health Center in Waingapu - Yosephina E. S. Gunawan; Sofia Rhosma Dewi (Poltekkes Kemenkes Kupang, 2018)
Background: Hypertension is a chronic condition that requires management that can provide long-term effects through lifestyle modification. Lifestyle modification in patients with hypertension can be observed through the health behavior of hypertensive patients. Methods: This study was a descriptive analytic study with a survey method that aimed to determine the health behavior of primary hypertensive patients in the work area of ​​Waingapu Health Center in 2017. This study involved 45 respondents who were taken with simple random sampling technique from a total population of 122 people. Data were collected through questionnaires and then analyzed by descriptive statistical tests. Results: The results of this study were 4 articles found in the database showed that there was an effect of yoga therapy in lowering blood pressure of hypertensive patients. Conclusion: Mature age supported by a high enough education can form a good attitude about hypertension which is then manifested through a healthy behavior.